P5 The critical situations (CRISIS) course and training in rare, life-threatening and time-critical emergencies. (November 2018) - Robinson, David; Clegg, Eleanor; Harrison, Tracey
Abstract : Background: The Critical Situations (CRISIS) course is a simulation and technical skills course for Emergency Medicine Higher Specialist Trainees (EM HSTs) involving simulated scenarios in 1. anaphylaxis with upper airway obstruction, 2. penetrating chest trauma and 3. massive PE in pregnancy with cardiac arrest. The associated skills sessions cover surgical airway, thoracotomy and perimortem C-section. We aimed to determine the impact of the course on the confidence of EM HSTs in managing these rare, life-threatening, time-critical emergencies. Summary of work: 6 CRISIS courses have been held in Bradford between May 2014 and November 2016 (35 EM HSTs). Candidates were asked to rate their pre and post course confidence using a standard Likert scale (score 1 to 5). Some questions focused upon the technical elements of managing each clinical scenario and performing each skill. Other questions asked about the non-technical skills we expected candidates to acquire, e.g. anticipation, communication, leadership, prioritising, delegating, re-evaluation and managing distractions. Mean confidence levels before and after the course were compared. To identify the most valued aspects of the course we calculated the mean improvement in confidence in the pooled technical skills and compared this to the pooled non-technical skills. Summary of results: We found that the mean confidence in all individual domains improved significantly (p<0.05 for all domains, paired t test). There was an improvement of 0.535 in the non-technical skills but a greater improvement of 1.9 in the technical skills (p=0.0071, paired t test). Greater confidence in the procedural skills was most marked, with a mean increased confidence score of 2.69 for performing a perimortem C-section, 2.03 for thoracotomy and 1.2 for surgical cricothyroidotomy. Discussion and conclusions: The CRISIS course offers the opportunity for rare, time critical and life threatening scenarios to be experienced by candidates. We have demonstrated an overall improvement in the candidates' confidence to manage each scenario, and in particular increased confidence in performing rare technical skills. The CRISIS course is now hosted in Bradford, Hull and Leeds, with support from the Yorkshire and Humber School of Emergency Medicine, and it is a ARCP requirement for all local EM ST6 trainees to attend the course. Recommendations: We believe this course is the first of its kind in the UK providing training to EM trainees in these 3 scenarios using both simulation and technical skills facilities, and we recommend that similar training is offered to EM trainees in other regions.